Survey on Fibre Optic Deployment for Telecommunications Operators in Ghana: Coverage Gap, Recommendations and Research Directions (London Journal of Engineering Research, 2025)
This paper presents a comprehensive survey on the deployment of fibre optic networks for telecommunications operators in Ghana. It addresses the challenges encountered by operators using microwave transmission systems for backhauling traffic and emphasises the advantages of deploying fibre optic networks. The study delves into the coverage gap, provides recommendations, and outlines research directions to enhance the telecommunications infrastructure in Ghana. Additionally, it evaluates next-generation optical access technologies and architectures tailored to operators’ needs. The paper also investigates current technological solutions and regulatory, technical, and economic dimensions related to sharing mobile telecommunication networks in emerging countries. Overall, this paper offers valuable insights into fibre optic network deployment for telecommunications operators in Ghana and suggests strategies to meet the increasing demand for data and mobile applications.
Keywords: Speech Recognition Systems; Inclusive Digital Access; Multilingual Technologies; Telephone-based Interfaces; Digital Accessibility; Deep Learning; Crack Detection; YOLOv8n-cls; Infrastructure Monitoring; Concrete Cracks; Image Classification.; free radicals; DC high voltage electrochemical reation; electrochemical plasma; nano metal solution; enviromentally friendly watertreatment